Biomechanical analysis of a new cannulated screw for unstable femoral neck fractures - Chen, Zhigang; Chen, Feiyang; Xu, Xinbao; Li, Xin; Cui, Haidong; Zhang, Wen; Jiang, Dong; Zhang, Feixiang; Chen, Yinbing; Zhou, Shiran; Lyu, Shujun (Frontiers in Bioengineering and Biotechnology, 2024)
The treatment of unstable femoral neck fractures (FNFs) remains a challenge. In this study, a new cannulated screw for unstable FNFs was designed to provide a new approach for the clinical treatment of these injuries, and its biomechanical stability was analyzed using finite element analysis and mechanical tests.Methods: An unstable FNF model was established. An internal fixation model with parallel inverted triangular cannulated screws (CSs) and a configuration with two superior cannulated screws and one inferior new cannulated screw (NCS) were used.The biomechanical properties of the two fixation methods were compared and analyzed by using finite element analysis and mechanical tests.The NCS model outperformed the CSs model in terms of strain and stress distribution in computer-simulated reconstruction of the inverted triangular cannulated screw fixation model for unstable FNFs. In the biomechanical test, the NCS group showed significantly smaller average femoral deformation (1.08±0.15 mm vs. 1.50±0.37 mm) and fracture line displacement (1.43±0.30 mm vs. 2.01±0.47 mm).In the NCS group, the mean stiffness was significantly higher than that in the CSs group (729.37±82.20 N/mm vs. 544.83±116.07 N/mm), and the mean compression distance was significantly lower than that in the CSs group (2.87±0.30 mm vs.The NCS combined with two ordinary cannulated screws in an inverted triangle structure to fix unstable FNFs can provide better biomechanical stability than CSs and exhibit a length-and angle-stable construct to prevent significant femoral neck shortening.